Educational Differences in the Prevalence of Dementia and Life Expectancy with Dementia: Changes from 2000 to 2010. (16th April 2018) - Crimmins, Eileen M; Saito, Yasuhiko; Kim, Jung Ki; Zhang, Yuan S; Sasson, Isaac; Hayward, Mark D
Abstract: Objectives: This article provides the first estimates of educational differences in age-specific prevalence, and changes in prevalence over time, of dementia by education levels in the United States. It also provides information on life expectancy, and changes in life expectancy, with dementia and cognitively healthy life for educational groups. Method: Data on cognition from the 2000 and 2010 Health and Retirement Study are used to classify respondents as having dementia, cognitive impairment without dementia (CIND), or being cognitively intact. Vital statistics data are used to estimate life tables for education groups and the Sullivan method is used to estimate life expectancy by cognitive state. Results: People with more education have lower prevalence of dementia, more years of cognitively healthy life, and fewer years with dementia. Years spent in good cognition increased for most sex-education groups and, conversely, years spent with dementia decreased for some. Mortality reduction was the most important factor in increasing cognitively healthy life. Change in the distribution of educational attainment has played a major role in the reduction of life with dementia in the overall population. Discussion: Differences in the burden of cognitive loss by education point to the significant cost of low social status both to individuals and to society.